Biomechanical effect of inclined implants in fixed prosthesis: strain and stress analysis - Rodrigues, Vinícius Anéas; Tribst, João Paulo Mendes; Santis, Leandro Ruivo; Borges, Alexandre Luiz Souto; Nishioka, Renato Sussumu (Universidade Estadual Paulista Júlio de Mesquita Filho, 2018)
AbstractIntroductionImplant inclinations can be corrected using mini abutments at different angulations.ObjectiveTo analyze the influence of external hexagon implants in different inclinations (3 levels) on the microstrain distribution generated around three implants.MethodA geometric bone model was created through Rhinoceros CAD software (version 5.0 SR8, Mcneel North America, Seattle, WA, USA). Three implants (4.1 × 13 mm) were modeled and inserted inside the substrate at three different inclinations: 0º, 17º and 30º. Next, all groups received mini conical abutments, fixation screws and a simplified prosthesis. The final geometry was exported in STEP format to analysis software and all materials were considered homogeneous, isotropic and linearly elastic. An axial load (300N) was applied on the center of the prosthesis. An in vitro study was conducted with same conditions and groups for validating the tridimentional model.ResultStress was concentrated on the external area of the implants, in contact with the cortical bone and external hexagon. For the bone simulator, the strain increased in the peri-implant region according to the increase in the implant’s inclination. The difference between groups was significant (p = 0.000). The 30º group presented higher stress and strain concentration.ConclusionThe microstrain and stress increase around implants directly proportional to the increase of the installation angle.

ResumoIntroduçãoA inclinação dos implantes pode ser corrigida através de mini-pilares de diferentes angulações.ObjetivoAnalisar a influência de implantes com hexágono externo em diferentes inclinações (3 níveis) na distribuição de microdeformações geradas em torno de três implantes.MétodoUm modelo geométrico de osso foi criado através do software CAD Rhinoceros (versão 5.0 SR8, Mcneel North America, Seattle, WA, EUA). Três implantes (4,1 × 13 mm) foram modelados e inseridos no interior do substrato em três diferentes inclinações: 0º, 17º e 30º. Em seguida, todos os grupos receberam mini-pilares cônicos, parafusos de fixação e prótese simplificada. A geometria final foi exportada em formato STEP para software de análise e todos os materiais foram considerados homogêneos, isotrópicos e linearmente elásticos. Uma carga axial (300N) foi aplicada no centro da prótese. Um estudo in vitro foi conduzido com as mesmas condições e grupos para validar o modelo tridimensional.ResultadoA concentração de tensão ocorreu na área externa dos implantes, em contato com o osso cortical e o hexágono externo. Para o simulador ósseo, a deformação aumentou na região peri-implantar de acordo com o aumento da inclinação do implante. A diferença entre os grupos foi significativa (p = 0.000). O grupo de 30º apresentou maior concentração de tensão e deformação.ConclusãoO aumento da microdeformação e das tensões ao redor dos implantes aumenta diretamente proporcional ao aumento do ângulo de instalação.
Efeito biomecânico de implantes inclinados em prótese fixa: analise das tensões e deformações
Keywords: Finite element analyses; dental implant; fixed prosthesis; Análises de elementos finitos; implante dentário; prótese fixa